2016
DOI: 10.1007/s00535-016-1292-z
|View full text |Cite
|
Sign up to set email alerts
|

Indigo Naturalis ameliorates murine dextran sodium sulfate-induced colitis via aryl hydrocarbon receptor activation

Abstract: IN and indigo ameliorated murine colitis through AhR signaling activation, suggesting that AhR could be a promising therapeutic target for UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 43 publications
1
78
1
Order By: Relevance
“…As mentioned above, we did not observe any effect on DSS colitis despite previous papers describing alleviation of DSS colitis by IND [41,42]. The dose used was similar [41], but the preparation of IND used was different from ours, and this may have led to discrepancies in the results.…”
Section: Discussioncontrasting
confidence: 54%
“…As mentioned above, we did not observe any effect on DSS colitis despite previous papers describing alleviation of DSS colitis by IND [41,42]. The dose used was similar [41], but the preparation of IND used was different from ours, and this may have led to discrepancies in the results.…”
Section: Discussioncontrasting
confidence: 54%
“…[24][25][26][27] More recently, IN has been shown to improve dextran sulfate sodium-induced colitis in a mouse model via an AhR/IL-22-mediated pathway. 28 However, recent studies have also shown other mechanisms of AhR signaling in terms of the induction of IL-10 receptor expression on intestinal epithelia, 29 IL-10 production in macrophages, 30 the induction of regulatory T cells, 31 and the negative regulation of the NLRP3 inflammasome. 32 Regardless, IN with different mechanisms from the current standard treatments may be beneficial for cases in which the efficacy of immunosuppressant or biologics is inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AhR ligands are crucial for activating AhR‐expressing type 3 innate lymphoid cells in the mucosa to produce IL‐22 . IL‐22 promotes mucosal healing by stimulating mucus production and goblet cell reconstitution under inflammatory conditions . Furthermore, AhR signaling has also been reported to induce immune tolerance with the production of IL‐10 .…”
Section: Discussionmentioning
confidence: 99%